Terraranans of the Lost World: a new species of Pristimantis (Amphibia, Craugastoridae) from Abakapá-tepui in the Chimantá massif, Venezuelan Guayana, and additions to the knowledge of P. muchimuk - Rojas-Runjaic, Fernando J. M.; Salerno, Patricia E.; Señaris, J. Celsa; Pauly, Gregory B. (Zootaxa, 2013)
A new frog of the genus Pristimantis is named and described from the summit of Abakapá-tepui in the Chimantá massif, south-eastern Venezuela. The new species is known from two adult specimens and is the second craugastorid species described from this massif. It can be readily distinguished from all congeners inhabiting the highlands of the Guiana Shield by the unique combination of the following characters: dorsal skin shagreen and ventral skin coarsely areolate, tympanum small and ill-defined, vocal slits absent in males, finger I shorter than II, thumbs with two whitish and non-spinous nuptial pads in adult males, fingers and toes with broad lateral fringes, basal webbing between all toes, throat and chest nacreous white in life. Also, based on five specimens of Pristimantis muchimuk recently collected from Churí-tepui, we provide new information on this little known species, including an amended diagnosis, notes on morphology, color variation, advertisement calls, and natural history.